Análise Geoquímica dos Sedimentos de Fundo do Arroio do Salso, Porto Alegre - RS - Brasil - SOARES, MARIA CRISTINA CERVEIRA; MIZUSAKI, ANA MARIA PIMENTEL; GUERRA, TERESINHA; VIGNOL, MARIA LÍDIA (Pesquisas em Geociências, 2004)
This paper presents the results of a study performed on bedload samples from the Salso Creek in the Porto Alegre City (Rio Grande do Sul State) rural area where agricultural and pastoral activities are carried out within urban areas. Sediment sampling took place on the 16th September 2001 (winter) and 21th January 2002 (summer), at five sites along the Salso Creek. The Salso Creek bed load changes from granules and pebbles (upstream reaches), through coarse- to medium-grained sand (mid reaches) to fine-to very fine-grained sand in the Salso Creek mouth region. Organic matter content increases throughout the summer low discharge due to the accumulation of the suspended load on the creek bed surface. Grains larger then 0.062 mm feature the following estimated mineralogical composition: feldspar (55-50%), quartz (30-40%), opaque (5-10%) and acessory (5-10%) minerals. Among the finegrained sediments (< 0.062 mm) kaolinite dominates being followed by a minor amount of muscovite/illite as well as quartz, feldspar and smectite traces. The chemical composition of the fine-grained sediments reveals that, among the major (Al, Fe, Mn, Ca, Mg, Na and K) and trace (Cr, Cu, Ni, Pb and Zn) analyzed elements, the Al content is high, probably a result of the kaolinite-rich (Al4(Si4O10)(OH)8) composition of the fine-grained fraction. GeoAccumulation Index calculation shows no significant accumulation of any of the analyzed elements within the finegrained fraction, hence indicating slightly to moderately polluted sediments. On the other hand Contamination Factor computation for the sediments fine-grained fraction pointed out a Cu, Ni and Zn enrichment, indicating considerable to high contamination, especially for those places directly under domestic sewerage influence. These elements are probably being concentrated in the fine-grained fraction of the bed load.